2016
DOI: 10.1016/j.cognition.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

From faces to hands: Changing visual input in the first two years

Abstract: Human development takes place in a social context. Two pervasive sources of social information are faces and hands. Here, we provide the first report of the visual frequency of faces and hands in the everyday scenes available to infants. These scenes were collected by having infants wear head cameras during unconstrained everyday activities. Our corpus of 143 hours of infant-perspective scenes, collected from 34 infants aged 1 month to 2 years, was sampled for analysis at 1/5 Hz. The major finding from this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
229
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(247 citation statements)
references
References 86 publications
17
229
1
Order By: Relevance
“…Egocentric vision is an emerging field that studies vision from the individual perceiver's point of view; a viewpoint dependent on momentary location and bodily orientation [38][39][40][41]. Research with infants, toddlers and adults (e.g.…”
Section: (B) Visual Statistics As the Proposed Solutionmentioning
confidence: 99%
“…Egocentric vision is an emerging field that studies vision from the individual perceiver's point of view; a viewpoint dependent on momentary location and bodily orientation [38][39][40][41]. Research with infants, toddlers and adults (e.g.…”
Section: (B) Visual Statistics As the Proposed Solutionmentioning
confidence: 99%
“…The head-camera data generated by these infants is part of a growing corpus of infant-perspective scenes collected to understand the natural statistics of early visual experience and how it changes with age. Thus, twenty-two of the infants in the present analysis (all younger than 13 months of age) contributed head-camera data to the earlier study (Jayaraman et al, 2015) that first reported an age-related decline in the faces in view within the first year; 34 of the infants contributed head camera images to the study (Fausey et al, in press) that analyzed hands in infant-perspective scenes. Two infants in the present study were new to the corpus.…”
Section: Methodsmentioning
confidence: 91%
“…Because humans are social animals and because human faces provide important social information, it seems reasonable to assume that faces are visually prevalent throughout life (e.g., Calder & Young, 2005; Cohen & Cashon, 2001; Haxby et al, 2000; Kadosh & Johnson, 2007; Kanwisher & Yovel, 2006; McKone et al, 2007; Nelson, 2003; Tarr & Gauthier, 2000; Zhao & Bentin, 2008). However, recent research using head cameras suggests potentially significant changes in the faces in infant views (Fausey et al, in press; Jayaraman et al, 2015; Sugden et al, 2014). The two experiments reported here were designed to answer the question of whether this age-related decline in faces was about a change in the frequency of people positioned in front of the infant or more specifically about the frequency of faces in front of the infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young children extend the duration of sustained attention to an object while an older person shows attention to that object, suggesting how social interactions can support the development of sustained attention in the particular context of handling objects (27). The visual salience to humans of others' hand movements is evident by the second year of life, when toddlers shift their visual attention toward another person handling an object from predominantly toward the face to predominantly toward the hands (28).…”
Section: Social Experience Influences the Development Of Attentionmentioning
confidence: 99%